The Profile of Microbiological Pathogens in Diabetic Foot Ulcers - Chai, Wei; Wang, Yuqing; Zheng, Huancheng; Yue, Song; Liu, Yan; Wu, Yili; Li, Xuezhi (Frontiers in Medicine, 2021)
A main complication of diabetes mellitus is diabetic foot, which renders the foot susceptible to infection and can eventually lead to non-traumatic limb amputation due to the deterioration of foot ulcers. Investigation of the pathogen spectrum is critical for diabetic foot infection management and prevention. In the current study characteristics of the pathogen spectrum and their antibiotic susceptibility in patients with diabetic foot infection were analyzed. Secretions from the diabetic foot ulcers of 102 patients were cultured, and pathogen spectrums were identified using test cards. Antibiotic susceptibility was assessed via the Kirby-Bauer assay. Pathogen spectrums varied with age, duration of diabetes, blood sugar control, and the initial cause of ulcers. All bacteria detected were susceptible to at least one antibiotic, but the antibacterial efficacy of several commonly used antibiotics decreased from 2016 to 2019. The results of the study indicate that bacterial culture and antibiotic susceptibility testing is an essential component of informed antibiotic administration in patients with diabetic foot infection, and that the abuse of antibiotics should be strictly restrained to control the generation of antibiotic-resistant strains.